Population structure of Sclerotinia sclerotiorum in crop and wild hosts in the UK. (25th May 2012) - Clarkson, J. P.; Coventry, E.; Kitchen, J.; Carter, H. E.; Whipps, J. M.
<x xml:space="preserve">Abstract</x> Sclerotinia sclerotiorum is an important pathogen of many crop plants which also infects wild hosts. The population structure of this fungus was studied for different crop plants and Ranunculus acris (meadow buttercup) in the UK using eight microsatellite markers and sequenced sections of the intergenic spacer (IGS) region of the rRNA gene and the elongation factor 1‐alpha (EF) gene. A total of 228 microsatellite haplotypes were identified within 384 isolates from 12 S. sclerotiorum populations sampled in England and Wales. One microsatellite haplotype was generally found at high frequency in each population and was distributed widely across different hosts, locations and years. Fourteen IGS and five EF haplotypes were found in the 12 populations, with six IGS haplotypes and one EF haplotype exclusive to buttercup. Analysis of published sequences for S. sclerotiorum populations from the USA, Canada, New Zealand and Norway showed that three of the IGS haplotypes and one EF haplotype were widely distributed, while eight IGS haplotypes were only found in the UK. Although common microsatellite and IGS/EF haplotypes were found on different hosts in the UK, there was evidence of differentiation, particularly for one isolated population on buttercup. However, overall there was no consistent differentiation of S. sclerotiorum populations from buttercup and crop hosts. Sclerotinia sclerotiorum therefore has a multiclonal population structure in the UK and the wide distribution of one microsatellite haplotype suggests spatial mixing at a national scale. The related species S. subarctica was also identified in one buttercup population.